1992
DOI: 10.1093/jmedent/29.6.960
|View full text |Cite
|
Sign up to set email alerts
|

Food Ingestion and Digestive Enzymes in Larval Aedes aegypti and Ae. albopictus (Diptera: Culicidae)

Abstract: Frequency of the labral brush movements of first, second, and fourth instars of Aedes aegypti (L.) and Aedes albopictus (Skuse) was studied comparatively in the laboratory. A frequency of 197 strokes per min for the first and second instars was observed in the former species compared to 118 strokes per min in the latter species. A faster ingestion rate of algal cells also was observed in first and second instars of Ae. aegypti (mean 57.5 cells per s) compared with first and second instars of Ae. albopictus (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
4
14
0
4
Order By: Relevance
“…The band size range from ~25 to 250 kDa. The proteolytic activities of this mosquito have received little study, focusing mainly on larval activities and on comparisons with A. aegypti [38]. Comparisons between the previously reported peptidase profiles from the larval and pupal stages of A. albopictus [33] with the profile from the adult midgut obtained here reveals a similar banding pattern of enzymatic activity, suggesting that the peptidases expressed as part of the adult proteolytic machinery are already expressed in the pre-imaginal stages, where they mainly seem to play roles in digestion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band size range from ~25 to 250 kDa. The proteolytic activities of this mosquito have received little study, focusing mainly on larval activities and on comparisons with A. aegypti [38]. Comparisons between the previously reported peptidase profiles from the larval and pupal stages of A. albopictus [33] with the profile from the adult midgut obtained here reveals a similar banding pattern of enzymatic activity, suggesting that the peptidases expressed as part of the adult proteolytic machinery are already expressed in the pre-imaginal stages, where they mainly seem to play roles in digestion.…”
Section: Resultsmentioning
confidence: 99%
“…These activities were again strongly inhibited by PMSF and TLCK, but not by TPCK, (Figure 3B) corroborating the in-gel results. The occurrence of trypsin-like serine peptidases has been described in the larvae of A. aegypti and A. albopictus using both in-solution assays [38,39] and zymographic analysis [33,43]. The main peptidases detected in other Diptera species also belong to the serine peptidase class [42,44,45].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports (Yang and Davies, 1971;Ho et. al., 1992; GenBank accession numbers AF487334, AF487426, and AY198134) have indicated that Ae aegypti larvae synthesize both trypsin and chymotrypsin-like enzymes.…”
Section: Synthesis Of Trypsin-and Chymotrypsin-like Enzymes In the MImentioning
confidence: 91%
“…However, its abundance in the adult CNS may indicate that the hormone has other functions. Yang and Davies (1971) and Ho et al (1992) reported that trypsin and chymotrypsin are the main digestive enzymes in Ae. aegypti.…”
Section: March 2004mentioning
confidence: 99%
See 1 more Smart Citation